High-order upwinding and the hydraulic jump - Ferreira, V. G.; Tome, M. F.; Mangiavacchi, N.; Castelo, A.; Cuminato, J. A.; Fortuna, A. O.; McKee, S. (Wiley-Blackwell, 2002)
This work is concerned with the computation of incompressible axisymmetric and fall three-dimensional free-surface flows. In particular, the circular-hydraulic jump is simulated and compared with approximate analytic solutions. However, the principal thrust of this paper is to provide a real problem as a test bed for comparing the many existing convective approximations. Their performance is compared; SMART, HLPA and VONOS emerge as acceptable upwinding methods for this problem. Copyright (C) 2002 John Wiley Sons, Ltd.
Keywords: Navier-Stokes; free-surface flows; finite differences; upwinding; high-order discretization; bounded numerical scheme; hydraulic jump